Empirical research on the diffusion effect of ICT innovation diffusion and prediction in China - Wenyu HU; Wenju WANG (Dianxin kexue)
Based on the characteristics of information and communication technology (ICT) in China,an empirical study was made on the diffusion effect of ICT innovation using Bass extension model.The results show that the curve fitting estimation effect of genetic algorithm was remarkable.In addition,non-cumulative adopter model was used to empirically analyze the diffusion effect of ICT innovation from the aspects of technology evolution,business,region and provinces.It was concluded that innovation diffusion was significantly driven by innovation effect along with the evolution of ICT,especially 3G/4G,broadband Internet,digital TV and their convergent business.Finally,the non-cumulative Bass model using genetic algorithm were used to predict the user size of fixed-line,mobile,broad-band,radio and television in the next five years.